The interplay between metabolic alterations, diastolic strain rate and exercise capacity in mild heart failure with preserved ejection fraction: a cardiovascular magnetic resonance study - Masliza Mahmod; Nikhil Pal; Jennifer Rayner; Cameron Holloway; Betty Raman; Sairia Dass; Eylem Levelt; Rina Ariga; Vanessa Ferreira; Rajarshi Banerjee; Jurgen E. Schneider; Christopher Rodgers; et al. (Journal of Cardiovascular Magnetic Resonance, 2018)
Abstract Background Heart failure (HF) is characterized by altered myocardial substrate metabolism which can lead to myocardial triglyceride accumulation (steatosis) and lipotoxicity. However its role in mild HF with preserved ejection fraction (HFpEF) is uncertain. We measured myocardial triglyceride content (MTG) in HFpEF and assessed its relationships with diastolic function and exercise capacity. Methods Twenty seven HFpEF (clinical features of HF, left ventricular EF >50%, evidence of mild diastolic dysfunction and evidence of exercise limitation as assessed by cardiopulmonary exercise test) and 14 controls underwent 1H-cardiovascular magnetic resonance spectroscopy (1H-CMRS) to measure MTG (lipid/water, %), 31P-CMRS to measure myocardial energetics (phosphocreatine-to-adenosine triphosphate - PCr/ATP) and feature-tracking cardiovascular magnetic resonance (CMR) imaging for diastolic strain rate. Results When compared to controls, HFpEF had 2.3 fold higher in MTG (1.45 ± 0.25% vs. 0.64 ± 0.16%, p = 0.009) and reduced PCr/ATP (1.60 ± 0.09 vs. 2.00 ± 0.10, p = 0.005). HFpEF had significantly reduced diastolic strain rate and maximal oxygen consumption (VO2 max), which both correlated significantly with elevated MTG and reduced PCr/ATP. On multivariate analyses, MTG was independently associated with diastolic strain rate while diastolic strain rate was independently associated with VO2 max. Conclusions Myocardial steatosis is pronounced in mild HFpEF, and is independently associated with impaired diastolic strain rate which is itself related to exercise capacity. Steatosis may adversely affect exercise capacity by indirect effect occurring via impairment in diastolic function. As such, myocardial triglyceride may become a potential therapeutic target to treat the increasing number of patients with HFpEF.